2015
DOI: 10.1002/ccd.25166
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of renal denervation in elderly patients with resistant hypertension

Abstract: According to our findings, a similar magnitude of BP reduction as reported in previous trials can be expected in elderly patients. Elderly patients with rHTN should not be excluded from renal denervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…While RDN remained an experimental procedure in the USA, pending the results of Symplicity HTN-3 [8] (NCT01418261), a large randomized controlled trial including a sham procedure, reimbursement of RDN was granted in Germany, Australia, the Netherlands, Switzerland and Sweden, leading to an outburst in the number of procedures performed (>5000 worldwide, of which 600 in a single German centre) (). RDN was applied indiscriminately to patients with white-coat resistant hypertension [9], isolated systolic hypertension [10], stenotic [11] or stented [12] renal arteries and even in a patient with Münchausen syndrome [13]. Finally, based almost exclusively on observational, small studies, RDN was proposed as a potential treatment in a host of medical conditions, including chronic kidney disease, atrial fibrillation, heart failure, obstructive sleep apnoea, metabolic syndrome and polycystic ovary syndrome [14].…”
Section: From Symplicity Htn-2 To Symplicity Htn-3: a Predictable Faimentioning
confidence: 99%
“…While RDN remained an experimental procedure in the USA, pending the results of Symplicity HTN-3 [8] (NCT01418261), a large randomized controlled trial including a sham procedure, reimbursement of RDN was granted in Germany, Australia, the Netherlands, Switzerland and Sweden, leading to an outburst in the number of procedures performed (>5000 worldwide, of which 600 in a single German centre) (). RDN was applied indiscriminately to patients with white-coat resistant hypertension [9], isolated systolic hypertension [10], stenotic [11] or stented [12] renal arteries and even in a patient with Münchausen syndrome [13]. Finally, based almost exclusively on observational, small studies, RDN was proposed as a potential treatment in a host of medical conditions, including chronic kidney disease, atrial fibrillation, heart failure, obstructive sleep apnoea, metabolic syndrome and polycystic ovary syndrome [14].…”
Section: From Symplicity Htn-2 To Symplicity Htn-3: a Predictable Faimentioning
confidence: 99%
“…However, a few studies have been designed, at least in part, to test prospectively the effect of RDN on BP in specific patient groups, e.g. elderly subjects [12]. …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] An additional seven studies that showed no decrease in 24-h ambulatory blood pressure after renal denervation were also not mentioned. [7][8][9][10][11][12][13] Admittedly, patient numbers in these 11 trials were small (n = 6-24), and the majority of clinical studies reported have shown a reduction in blood pressure with renal denervation. Nevertheless, being aware of these negative findings is important.…”
mentioning
confidence: 99%
“…Nevertheless, being aware of these negative findings is important. [3][4][5][6][7][8][9][10][11][12][13] For example, Fadl Elmula et al reported that in six patients with true resistant hypertension, office blood pressure remained unchanged at 1, 3 and 6 months after renal denervation. 3 This study was the first to use witnessed intake of medication to exclude patients with poor drug adherence.…”
mentioning
confidence: 99%